How to write like Chekhov : advice and inspiration, straight from his own letters and work - Chekhov, Anton Pavlovich, 1860-1904 (Da Capo Lifelong, 2008)
"Conciseness is the sister of talent"--And other essential, illuminating observations and advice from Anton Chekhov, one of the most deeply revered writers of all time.